Soundscape in Times of Change: Case Study of a City Neighbourhood During the COVID-19 Lockdown - Lenzi, Sara; Sádaba, Juan; Lindborg, PerMagnus (Frontiers in Psychology, 2021)
The COVID19 lockdown meant a greatly reduced social and economic activity. Some people remarked that the urban soundscape was changing for the better. But are these anecdotal reports based in truth? This article presents a case study of the human perception of environmental sounds in an urban neighbourhood in the Basque Country between 15 March and 25 May 2020. We collected observations, field audio recordings, photography, and diary notes on 50 days. Experts in soundscape and architecture were presented with the recordings, in randomized order, and made two separate perceptual analyses. One group rated the recordings for Pleasantness and Eventfulness and a partly overlapping group annotated perceived sound events with free-form semantic labels. The labels were systematically classified allowing an estimation of the relative amounts of Natural, Human, and Technological sounds. Loudness and three descriptors developed for bioacoustics were extracted computationally. Analysis showed that Eventfulness, Acoustic Complexity, and Acoustic Richness increased significantly over the time period, while the amount of Technological sounds decreased. These observations were interpreted as reflecting changes in people’s outdoor activities and behaviour, evidenced in an increased presence of Human sounds of voices and walking, and a significant shift from motorised vehicles towards personal mobility devices, again evidenced by perceived sounds. An integrated analysis of all sources pointed at the temporary suspension of human outdoor activity as the main reason for such a change. In the third phase, the progressive comeback of human beings to the neighborhood’s streets and the usage of personal mobility vehicles seem to be responsible for a clear increase in Eventfulness and Loudness even in the context of an overall decrease of Technological sounds. Indoor human activity shared through open windows and an increased presence of birdsong emerge as a novel characteristic element of the local urban soundscape. We discuss how such changes in the acoustic environment of the site studied, in measurements and as perceived by humans, point towards soundscape being a crucial component of a comprehensive urban design strategy that aims to improve health and quality of life for increasingly large and dense populations in the future.